Design and Study of Pre-stretching and Disassembling Device for Double-row Chain - Wang Shukun; Xu Yefeng; Liu Dongliang; Zhao Xudong; Shen Jiajun (Jixie chuandong)
Aiming at the pre-stretching and disassembling link in the manufacturing process of double-row chain, a new type of pre-stretching and disassembling device for double-row chain is designed. The device consists of two modules of pre-stretching and disassembling. The pre-stretching module uses hydraulic cylinder to load to move the associated sprockets and then pre-stretching sprocket between groups. The disassembling module uses pneumatic sliding table to drive chain insert plate to stabilize the chain, the pneumatic-hydraulic booster cylinder to drive punching nails to remove pin shafts, and the cylinder to drive chain pusher plate to push chain plate. The structure of the pre-stretching and disassembling has high degree of conversion, good interchangeability of vulnerable parts, can effectively realize the function of dynamic pre-stretching and disassembly of double-row chain.